Prenatal maternal stress and wheeze in children: novel insights into epigenetic regulation - Trump, Saskia; Bieg, Matthias; Gu, Zuguang; Thürmann, Loreen; Bauer, Tobias; Bauer, Mario; Ishaque, Naveed; Röder, Stefan; Gu, Lei; Herberth, Gunda; Lawerenz, Christian; Borte, Michael; et al. (Scientific reports, 2016)
Psychological stress during pregnancy increases the risk of childhood wheeze and asthma. However, the transmitting mechanisms remain largely unknown. Since epigenetic alterations have emerged as a link between perturbations in the prenatal environment and an increased disease risk we used whole genome bisulfite sequencing (WGBS) to analyze changes in DNA methylation in mothers and their children related to prenatal psychosocial stress and assessed its role in the development of wheeze in the child. We evaluated genomic regions altered in their methylation level due to maternal stress based of WGBS data of 10 mother-child-pairs. These data were complemented by longitudinal targeted methylation and transcriptional analyses in children from our prospective mother-child cohort LINA for whom maternal stress and wheezing information was available (n = 443). High maternal stress was associated with an increased risk for persistent wheezing in the child until the age of 5. Both mothers and children showed genome-wide alterations in DNA-methylation specifically in enhancer elements. Deregulated neuroendocrine and neurotransmitter receptor interactions were observed in stressed mothers and their children. In children but not in mothers, calcium- and Wnt-signaling required for lung maturation in the prenatal period were epigenetically deregulated and could be linked with wheezing later in children’s life.